Aprender brincando na educação infantil: jogos e brincadeiras tradicionais - TEIXEIRA, Cristianne do Carmo (2024)
Considering that “play” is the main activity of the child, in which he expresses his interaction with the world, his values, ways of thinking, acting and knowing how to do. And what game and play, besides educating, meet a natural need of the child. We aim from this article, which is fun in early childhood education, as a facilitator of cognitive and motor skills. Knowing that playful activities such as games, play and toys are part of the world of children, help in physical, cognitive and social development. Our research is bibliographic and is based on texts on the theme Ludicity from the conceptualization of Cipriano Luckesi and Tizuko Kishimoto. Our interest in the theme “Learning through play in early childhood education: traditional games and games”, arose from the reading of the texts on that theme that would serve as the basis for the production of the event “I Journey of games, toys and games” held by Pedagogy class 2018 of the UFPA - Soure”, in which we were encouraged to produce educational games and think about the rescue of games of old generations. Given that many teachers find it difficult to share certain knowledge, which could easily be passed on through play activities. At the end of the course, we concluded that directed play provides children with a pleasant and interesting environment, thus enabling the learning of skills useful to their social and affective life.